Generation and sex differences in sensation seeking: Results of family study - Butković, Ana (Array, 2003)
Previous research regarding sex and age differences for sensation seeking in English, American, Canadian, and Australian samples showed clear sex differences and a decline of sensation seeking with age. Form V of the Sensation Seeking Scale (Zuckerman, Eysenck & Eysenck, 1978) was administered to a Croatian sample of 151 high school students and their 266 parents. The results show that parents had lower scores than their children, consistent with the hypothesis that sensation seeking declines with age. Male subjects scored higher on the total Sensation Seeking, and Thrill and Adventure Seeking, Disinhibition, and Boredom Susceptibility subscales than female subjects, while there was no difference between male and female subjects on Experience Seeking scale. Also, several sex-by-generation interactions were significant.